Comparing Energy Harvesting Efficiency between Solar Panels: Tracking the Sun vs Ground-Mounted 40 WP Panels - Brahmana, Kurnia; Panjaitan, Wardaini (Journal of Technomaterial Physics, 2024)
This experiment aimed to evaluate the energy efficiency of a solar tracking panel compared to a ground-fixed solar panel. A 40 WP solar panel with a time-tracking mechanism was used to monitor the sun's movement from morning to evening, while a static 40 WP ground-fixed solar panel was also studied for comparison.The study also included the energy consumption of a 12 V DC motor responsible for orienting the tracking panel to face the sun. Throughout the day, the tracking panel's position was continuously adjusted to align with the sun's position, facilitated by a microcontroller and a gyroscope. The energy consumed by the motor during the tracking process was accounted for. The net energy output of the tracking panel was computed by subtracting the energy expended in tracking from the total energy collected. Following the experimentation, the collected data was analyzed to determine the energy efficiency of the tracking panel in contrast to the ground-fixed panel. The findings revealed that the tracking panel exhibited a 15 percent increase in energy efficiency compared to the ground-fixed panel. These results emphasize the potential benefits of solar tracking technology in optimizing energy capture from solar panels. The implications of these findings are valuable for advancing the design and implementation of solar energy systems, offering increased efficiency and sustainability.